Spatial orientation of angular momentum vectors: a comparative study of i-band spirals in SDSS Redshift slices 0.13-0.14 and 0.14-0.15 - Kandangwa, Obihang; Karki, Prem Bahadur; Malla, Janak Ratna (BIBECHANA, 2026)
We comparatively studied the spatial orientation of angular momentum alignment of 20,000 spiral galaxies selected from the SDSS DR16 i-band photometry. The sample is divided into two intermediate redshift ranges: 0.13-0.14 and 0.14-0.15. The 2D parameters were converted into 3D spin orientations using Godlowskian Transformation, where the azimuthal angle is derived from the tangential formula. A “Virtual Control” simulation of 107 random galaxies was developed in the model of the survey to predict the expected distribution. Statistical analyses were performed to evaluate the randomness of the distributions. The statistical results show that while localized anisotropies exist in specific slices, the overall orientation of spin vectors is consistent with isotropy. The Fourier coefficients for both samples fall within the Hierarchy model of galaxy formation.